Development and validation of mPCR-CEFA for detecting multiple deletion and non-deletion thalassemia genotypes - Xu, Jingping; Ren, Baoyan; Fang, Qixun; Lin, Kangfeng; Xing, Xingan; Lin, Jingting (Frontiers in Genetics, 2025)
BackgroundThalassemia is a common hereditary blood disorder caused by genetic variants in globin genes, leading to abnormal hemoglobin production. Rapid and accurate genotyping is essential for molecular screening and prenatal genetic diagnosis to prevent the birth of individuals with severe forms of the disease.MethodsWe developed a multiplex PCR-capillary electrophoresis fragment analysis (mPCR-CEFA) method to detect 16 α-thalassemia and 24 β-thalassemia genotypes simultaneously. Genomic DNA extracted from clinical blood samples underwent a two-tube multiplex PCR amplification. The amplification products were analyzed using capillary electrophoresis to detect mutation peaks in different fluorescent channels and to calculate α1/α2 and Y1/Y2 ratios for genotype determination. The performance of mPCR-CEFA was validated against conventional methods, including Gap-PCR and PCR-RDB.ResultsThe α1/α2 and Y1/Y2 peak ratios exhibited stable and reproducible values, allowing for precise genotyping of thalassemia events involving homologous recombination, such as -α3.7, -α4.2, αααanti3.7, αααanti4.2 and HKαα. Mutation peaks in different fluorescent channels also facilitated the differentiation of various genotypes, including deletion and non-deletion types. The method demonstrated a high accuracy rate of 99.5%. It successfully detected complex compound genotypes like αCD 74α/−α4.2, βCD 17/βN and αWSα/--SEA, βCD 37/βN (or αWSα/--SEA, βCD 37/βCD 37), which were challenging for traditional approaches.ConclusionThe mPCR-CEFA method is a reliable, efficient, and scalable tool for genetic diagnosis of thalassemia. Its ability to detect multiple genotypes simultaneously and resolve complex cases makes it particularly valuable for large-scale screening and clinical applications. This approach holds significant potential for improving thalassemia prevention strategies and supporting public health efforts in high-prevalence regions.